Paracobitis abrishamchiani, a new crested loach from the southern Caspian Sea basin (Teleostei: Nemacheilidae) - Mousavi-Sabet, Hamed; Vatandoust, Saber; Geiger, Matthias F.; Freyhof, Jörg (Zootaxa, 2019)
Paracobitis abrishamchiani, new species, is described from the southern Caspian Sea basin, where it is found in the Babol, Haraz, Siah, Tajan, Talar and Kashpal River drainages. It is distinguished from P. hircanica and P. atrakensis, the two other Paracobitis species known from the Caspian Sea basin, by having scales on the flank posterior to the dorsal-fin origin and from its congeners in the Middle East by the position of its dorsal-fin origin, having a roundish posterior narial opening, and a colour pattern consisting of many widely spaced brown spots and blotches. It is further characterized by six diagnostic nucleotide substitutions and a minimum K2P distance of 4.3% to P. persa and 4.6% to P. malapterura in the mtDNA COI barcode region.